Peningkatan Kualitas Tenaga Pengajar Pondok Pesantren Melalui Sosialisasi Pemahaman tentang Peraturan Perundang-Undangan - Yasir, Muhammad; Suhana, Asep; Ismail, Diauddin; Muhammad Amin, Muzakir; Abdullah Lawang, Karimuddin (Indra Institute Research & Publication, 2024)
Islamic boarding schools (pondok pesantren) play a crucial role in shaping generations with strong moral character and Islamic values. However, the quality of teaching staff in these institutions often still requires improvement, particularly in understanding legal regulations relevant to the education sector. This community service activity aims to enhance the legal awareness and understanding of the teaching staff at Pondok Pesantren Dayah Jamiah Al-Aziziyah Batei Iliek, Samalanga, Bireuen, regarding the regulations governing education, especially within the pesantren environment. The method employed in this activity includes sosialisasis and interactive discussions using a participatory approach. The activity was attended by all teaching staff and was guided by experts in the fields of law and education. The results indicate an increase in the knowledge and awareness of the teaching staff about the importance of understanding regulations to support educational processes that align with legal standards. It is hoped that this activity can be continued through broader mentoring and outreach programs to strengthen the overall education system in Islamic boarding schools.